Peptidyl-prolyl cis/trans isomerases in GtoPdb v.2023.1 - Annett, Stephanie; Robson, Tracy (IUPHAR/BPS Guide to Pharmacology CITE, 2023)
Peptidyl-prolyl cis/trans isomerases (PPIases) are an enzyme family which catalyse the cis/trans isomerisation of proline peptide bonds to promote the folding and re-folding of peptides and proteins. Three subfamilies have been identified: cyclophilins, FK506-binding proteins and parvulins. Individual PPIases are overexpressed in a number of cancers [62], and family members have been targetted for immunosuppressant effects.